Land Cover Change Mangrove Ecosystem in the Coastal Area of Bungus Teluk Kabung Padang City - Fadhilah, Lamis Tharra; Kamal, Eni; Mustapha, Muzzneena Ahmad; Putra, Aprizon (Sumatra Journal of Disaster, Geography and Geography Education, 2019)
The mangrove ecosystem is an ecosystem that grows above the brackish marshes that are located on coastlines and influenced by the tides of the sea water. The conditions of the mangrove ecosystem continue to experience widespread decline and change in density especially on the coastal area of Bungus Teluk Kabung. The study was conducted in June – August 2019. The purpose of this research is the major analysis of the rate of change of mangrove land cover, analysis of perception/community opinion about the conditions and efforts made by the Government of the mangrove and analysis of the condition of the mangrove ecosystem. The method used is a quantitative approach to descriptive. The result is a mangrove land cover of 2009 covering an area of 80.71 ha while the year 2019 is 60.35 ha, the rate of change (-25,23%/10 year), the change in mangrove area with a change rate of-100% found in the location of Teluk Sirih where the year 2009 (8, 82ha), and the year 2019 (0 ha). The change occurred due to the construction of the PLTU of Teluk Sirih. With the increase of mangrove ecosystem in the area of Pertamina Jetty because of the rehabilitation of local government. Its expansion in the year 2009 (3.06 ha) became the year 2019 (3.96 ha) with the addition of 0.90 ha and the rate of change of 29.41%. NDVI values of 2009 in 0.60 with normal vegetation density conditions and the year 2019 NDVI values in 0.42 with good vegetation density conditions.